2022
DOI: 10.1177/20552076221089789
|View full text |Cite
|
Sign up to set email alerts
|

Associations among eHealth literacy, social support, individual resilience, and emotional status in primary care providers during the outbreak of the SARS-CoV-2 Delta variant

Abstract: Objective This study aimed to investigate eHealth literacy among primary care providers (PCPs) and explore its association with social support, individual resilience, anxiety, and depression during an outbreak of the SARS-CoV-2 Delta variant in Guangzhou, China. Methods A cross-sectional web-based survey was conducted in 18 community healthcare centers in Guangzhou, China. The responses of 600 PCPs were tagged as valid responses. Information pertaining to their background, eHealth literacy, anxiety, depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…The findings of this study support a direct relationship between eHealth literacy and social support, which is consistent with previous findings showing a relationship between higher eHealth literacy levels and greater social support (K. A. Kim et al, 2018; Xu et al, 2022). The findings in this study may be associated with individuals with higher eHealth literacy being able to better communicate and share information with each other in Web 2.0, which increases perceived social support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study support a direct relationship between eHealth literacy and social support, which is consistent with previous findings showing a relationship between higher eHealth literacy levels and greater social support (K. A. Kim et al, 2018; Xu et al, 2022). The findings in this study may be associated with individuals with higher eHealth literacy being able to better communicate and share information with each other in Web 2.0, which increases perceived social support.…”
Section: Discussionmentioning
confidence: 99%
“…These resources may be instrumental (tangible goods or services), informational (education or advice), appraisal (affirmation), or emotional (affection; Langford et al, 1997). In previous studies, eHealth literacy was found to relate positively with social support in patients with congestive heart failure (Chuang et al, 2019) and in primary health providers (Xu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The outcome for J-eHEALS was calculated as both continuous and categorical variables ( 53 ). For J-eHEALS scores, participants were divided into two categories (high or low literacy) relative to the median group value (median 23.00, IQR: 18.00–27.00) based on previous studies ( 40 , 54 56 ).…”
Section: Methodsmentioning
confidence: 99%